The Usability and Effect of a Novel Intelligent Rehabilitation Exergame System on Quality of Life in Frail Older Adults: Prospective Cohort Study - Chien-Hsiang Chang; Chun-Chun Wei; Wei-Chih Lien; Tai-Hua Yang; Bo Liu; Yimo Lin; Poh Thong Tan; Yang-Cheng Lin (JMIR Serious Games)
Abstract BackgroundAging in older adults results in a decline in physical function and quality of daily life. Due to the COVID-19 pandemic, the exercise frequency among older adults decreased, further contributing to frailty. Traditional rehabilitation using repetitive movements tends not to attract older adults to perform independently. ObjectiveIntelligent Rehabilitation Exergame System (IRES), a novel retro interactive exergame that incorporates real-time surface electromyography, was developed and evaluated. MethodsFrail older adults were invited to use the IRES for rehabilitation using lower limb training twice per week for 4 weeks. Participants were required to have no mobility or communication difficulties and be willing to complete the 4-week study. The enrolled cohort had baseline scores ranging from 1 to 5 on the Clinical Frailty Scale, as described by Rockwood et al. Three major lower limb movements (knee extension, plantar flexion, and dorsiflexion) were performed 20 times for each leg within 30 minutes. The surface electromyography collected and analyzed muscle potential signals for review by health care professionals to customize the protocol for the next training. The System Usability Scale (SUS) and Taiwanese version of the EuroQol-5 Dimensions (EQ-5D) were administered after completing the first (week 1, baseline) and last training (week 4, one-month follow-up) to evaluate the usability of the IRES and its effects on the quality of life of participants. ResultsA total of 49 frail older adults (mean age 74.6 years) were included in the analysis. The usability of the IRES improved according to the mean SUS score, from 82.09 (good) at baseline to 87.14 (good+) at 1-month follow-up. The willingness to use (t96Pt96Pt96Pt47Pt47Pt96P ConclusionsThe novel IRES proposed in this study received positive feedback from frail older adults. Integrating retro-style exergame training into rehabilitation not only improved their rehabilitation motivation but also increased their learning, system operability, and willingness to continue rehabilitation. The IRES provides an essential tool for the new eHealth care service in the post–COVID-19 era.